Bioinspired optimization methods and their applications : 8th International Conference, BIOMA 2018, Paris, France, May 16-18, 2018, Proceedings /: 8th International Conference, BIOMA 2018, Paris, France, May 16-18, 2018, Proceedings. (2018) - Unknown
No abstract available